Influence of Substitution of Soybean Meal with Detoxified Neem (Azadirachta indica) Seed Cake on Growth and Nutrient Use in Goat Kids - Kumar, Dharmendra; Parnerkar, Subhash (Indian Journal of Animal Nutrition, 2018)
Marwari male goat (Capra hircus) kids (18) of age 6-8 months old (BW 16.08±0.08 kg) were randomly allotted to 3 groups of 6 each to study the effect of replace on growth and nutrient use. The group dNC-0 served as control whereas groups dNC-25 and dNC-75 were fed detoxified neem cake (dNC) replacing dietary soybean protein at 25 and 75% level in the concentrate mixture of control group and the jowar (Sorghum bicolor) hay was fed ad lib. The dNC was similar in protein (48.2%) content but higher in fibre (9.3%), Ca (1.0 %) and ash (9.1%) compared to soybean meal. The DM intake ranged between 3.42 and 3.75 kg/100 kg BW and digestibility of nutrients was similar in all the groups. All the animals showed positive N, Ca and P balance without any significant differences among groups. The daily water ingested by the growing kids ranged between 1.98 and 2.22 g/ kg DMI. The average daily gain was 91±3, 84±2 and 81±3 g in groups dNC-0, dNC-25 and dNC-75, respectively which was statistically similar. The average increase in heart girth, height and length were also statistically similar among groups. The efficiency of nutrient utilization in terms of DM, protein (CP and DCP) and energy (TDN) were not influenced by inclusion of dNC. The values of rumen pH, TVFA concentration, nitrogen fractions and cell mediated immunity were also similar in all the groups. It was concluded that detoxified neem seed cake could be incorporated in concentrate mixture by replacing soybean meal protein up to 75% level without affecting digestibility, total nutrients intake, growth performance, feed conversion efficiency and rumen fermentation pattern of growing kids.